Factores para el cometimiento del delito de violencia intrafamiliar en el cantón Salinas, durante el año 2024 - Valdiviezo Cristellot, Esteban Andrés (2025)
The figure of domestic violence as illegal and punishable behavior has taken legal force as societies have evolved through their impact on the family and social environment. The problem that covers domestic violence is currently relevant; to the point that it appears as the crime in the Comprehensive Organic Criminal Code, with the imposition of a penalty. To carry out an analysis of this social legal phenomenon, the content has been reviewed doctrinal postured by several legal and psychological scholars about the domestic violence with the purpose of exposing the theories and the types of domestic violence. With the objective of determining the factors that produce it. The research is located in canton Salinas, placed in the coastal region of our country, currently it is considered one of the most dangerous areas and, affected by the domestic violence; constitutes one of the largest causes that are processed in the prosecutor’s office and the criminal legal unit of the mentioned canton. The methods that worked as basis, are the analytical that was used to analyze the doctrine, the law, essential elements to investigate and explain the problem; also the qualitative method that allowed understand the social legal phenomenon researched its natural environment; using tools such as the interviews with key figures such as prosecutors who they presented their opinion based on their experience and which allowed them to conclude objectively. To determine the factors that cause domestic violence to occur.